Building battery physical test for the selection of players for badminton - Ali, Abbaas; Abdul Jabbar, Mohammed (Journal of Physical Education, 2015)
Played tests and measurements important and essential role in the arrival of the athletes to the upper levels and achievements of several operations, including the selection process, because the selection process helps coaches and specialists in the selection of players who have the physical and appropriate qualifications and that comply with the requirements for the game, and that the selection process contributes to the arrival of players to private levels if the selection at an early age being given the opportunity to player in the fitness and special skills for the game development, so the researcher built battery test physical-mobility on a sample of young players in badminton aged (14-17 years) was chosen as the descriptive style survey and using appropriate statistical methods to search, and then was to present and discuss the results of the factor analysis to build physical battery-motor, which resulted in four factors represent Battery learned and then gave the researcher the most important conclusions and recommendations that fit this Thesis